Dissolution and recovery of cellulose from pine wood bits in ionic liquids and a co-solvent component mixed system. (March 2019) - Liu, Ran; Zhang, Juan; Sun, Shuang; Bian, Yuhang; Hu, Yanhui
The dissolution and recovery of cellulose from pine wood bits with two types of ionic liquids and co-solvents were explored. The results revealed that 1-ethyl-3-methylimidazolium diethylphosphonate ionic liquid/dimethylsulfoxide (mass ratio 1:0.5) could dissolve pine cellulose within 8 min at 105°C. Moreover, the degree of polymerization of the regenerated cellulose reached 244. The dissolved cellulose could be regenerated from the component solution when water was added. Then, the regenerated cellulose was characterized by X-ray powder diffraction, Fourier-transform infrared spectroscopy, and thermal gravimetric analysis measurements. The results revealed that there was no derivatization of the reaction in the process of dissolution and that dissolving the pine cellulose was a direct process. The crystalline structure of the cellulose was converted from cellulose I to cellulose II after regeneration. The regenerated cellulose was also found to have good thermal stability.